Validitas Isi Model Latihan Tenvol Untuk Meningkatkan Kemampuan Smash Bolavoli - Ike Martha Nugrahani; Khoiril Anam (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
The purpose of this study was to determine the results of content validation of the TENVOL training model to improve volleyball smash skills. The media used is a tennis ball. The data used in this study are qualitative data and quantitative data. The data analysis technique used in this study used quantitative descriptive analysis techniques. The validity of this training model was obtained based on the assessment of two experts, namely 1 material expert in volleyball and 1 expert in volleyball coaching. The results of the expert assessment were then formulated with the Gregory formula. Based on the results of the assessment, it was found that the TENVOL training model to improve volleyball smash skills can be declared valid and relevant to use because the Vr value is 3.26 and is included in the range of 2.5 Vr 3.5. Therefore, it can be declared valid and feasible to be used at the next stage. The validation of this exercise model includes aspects such as objectives, material, presentation method, and the form of the exercise model. The suggestion from this research is that it can be tested further, both on small-scale product trials to large-scale usage trials, so that a better product for developing a smash training model using tennis ball media is obtained. And it can be developed further by adding more varied and interesting exercise models.